Thermokarst processes increase the supply of stabilizing surfaces and elements (Fe, Mn, Al, and Ca) for mineral–organic carbon interactions. (24th July 2022) - Monhonval, Arthur; Strauss, Jens; Thomas, Maxime; Hirst, Catherine; Titeux, Hugues; Louis, Justin; Gilliot, Alexia; du Bois d'Aische, Eléonore; Pereira, Benoît; Vandeuren, Aubry; Grosse, Guido; Schirrmeister, Lutz; et al.
Abstract: The stabilizing properties of mineral–organic carbon (OC) interactions have been studied in many soil environments (temperate soils, podzol lateritic soils, and paddy soils). Recently, interest in their role in permafrost regions is increasing as permafrost was identified as a hotspot of change. In thawing ice‐rich permafrost regions, such as the Yedoma domain, 327–466 Gt of frozen OC is buried in deep sediments. Interactions between minerals and OC are important because OC is located very near the mineral matrix. Mineral surfaces and elements could mitigate recent and future greenhouse gas emissions through physical and/or physicochemical protection of OC. The dynamic changes in redox and pH conditions associated with thermokarst lake formation and drainage trigger metal‐oxide dissolution and precipitation, likely influencing OC stabilization and microbial mineralization. However, the influence of thermokarst processes on mineral–OC interactions remains poorly constrained. In this study, we aim to characterize Fe, Mn, Al, and Ca minerals and their potential protective role for OC. Total and selective extractions were used to assess the crystalline and amorphous oxides or complexed metal pools as well as the organic acids found within these pools. We analyzed four sediment cores from an ice‐rich permafrost area in Central Yakutia, which were drilled (i) in undisturbed Yedoma uplands, (ii) beneath a recent lake formed within Yedoma deposits, (iii) in a drained thermokarst lake basin, and (iv) beneath a mature thermokarst lake from the early Holocene period. We find a decrease in the amount of reactive Fe, Mn, Al, and Ca in the deposits on lake formation (promoting reduction reactions), and this was largely balanced by an increase in the amount of reactive metals in the deposits on lake drainage (promoting oxidation reactions). We demonstrate an increase in the metal to C molar ratio on thermokarst process, which may indicate an increase in metal–C bindings and could provide a higher protective role against microbial mineralization of organic matter. Finally, we find that an increase in mineral–OC interactions corresponded to a decrease in CO2 and CH4 gas emissions on thermokarst process. Mineral–OC interactions could mitigate greenhouse gas production from permafrost thaw as soon as lake drainage occurs.